BIOREFINING SEBAGAI SALAH SATU TEKNOLOGI ALTERNATIF PADA PROSES PENGGILINGAN SERAT - Sari Farah Dina; Nina Elyani; Hoiror Rozikin; Lis Kusumawati (Center for Pulp and Paper, 2007)
The experiments of refining for long fibers bleached pulp using commercial cellulase enzyme (biorefining) has been done. Biorefining was carried out at consistency 1.5 %, pH 7.5, temperature 50 ± 5 °C, and freeness target 350 ml CSF. Cellulase addition varied at 0 – 0.6 % to fibers dry weight. The results showed that cellulase improves formation, brightness, and tensile index. But opacity, porosity, and tearing index decrease. Time for refining decrease with increasing of cellulase addition. At 0.4 cellulase addition the optimum improvements of sheet quality and energy saving observed.